Association of Embryology Education with Infertility Knowledge and Attitudes among Medical and Health Sciences Students - Emrah Zayman; Feyza İnceoğlu (İstanbul Gelişim Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Aim: The aim of this study is to compare infertility-related knowledge and attitudes among students from the Faculty of Medicine (basic and clinical phases) and the Faculty of Health Sciences (midwifery and nursing programs), and to investigate the association between embryology education and students' knowledge and attitudes toward infertility.Method: This cross-sectional study included 228 undergraduate students from the Faculties of Medicine and Health Sciences. The sample size was determined by power analysis and participants were recruited using the snowball sampling method. Data were collected through an online questionnaire consisting of a sociodemographic information form, infertility knowledge questions and the “Attitude Scale Toward Infertility”. Statistical analyses were performed using R version 4.3.1. Chi-square, independent samples t-test, Mann Whitney U, and Kruskal Wallis tests were applied as appropriate.Results: Students' responses to the infertility knowledge questions differed significantly according to gender, academic program, year of study, and receipt of embryology education (p<0.05). Medical students had significantly higher attitude scores toward infertility than health sciences students (47.81±7.58 vs. 36.72±3.62; t=−14.089, p<0.001). Likewise, students who had received embryology education demonstrated significantly higher attitude scores than those who had not (44.76±8.31 vs. 37.64±5.28; t=6.947, p<0.001).Conclusion: Medical students and students who had received embryology education exhibited greater infertility-related knowledge and more positive attitudes toward infertility than their counterparts. These findings suggest that strengthening embryology education may improve clinical awareness of infertility, support future healthcare professionals in the accurate management of infertility, facilitate psychosocial care, and contribute to reducing infertility-related social stigma.